Indonesian Literature’s Position in World Literature - Dina Amelia (Universitas Teknokrat Indonesia, 2016)
There are two most inevitable issues on national literature, in this case Indonesian literature. First is the translation and the second is the standard of world literature. Can one speak for the other as a representative? Why is this representation matter? Does translation embody the voice of the represented? Without translation Indonesian literature cannot gain its recognition in world literature, yet, translation conveys the voice of other. In the case of production, publication, or distribution of Indonesian Literature to the world, translation works can be very beneficial. The position of Indonesian literature is as a part of world literature. The concept that the Western world should be the one who represent the subaltern can be overcome as long as the subaltern performs as the active speaker. If the subaltern remains silent then it means it allows the “representation” by the Western.